\(-\frac{15}{2}x+\frac{3}{7}=\frac{6}{5}x-\frac{1}{2}\)
Đề như thế này à
\(-\frac{15}{2}x+\frac{3}{7}=\frac{6}{5}x-\frac{1}{2}\)
Đề như thế này à
Tìm x biết :
a, 4.(18 - 5x) - 12.(3x - 7) = 15.(2x - 16) - 6(x + 14)
b, 5.(3x + 5) - 4.(2x - 3) = 5x + 3.(2x + 12) + 1
c, 2.(5x - 8) - 3.(4x - 5) = 4.(3x - 4) + 11
d, (3x + 2)(2x + 9) - (x + 2)(6x + 1) = (x + 1) - (x - 6)
e, (8x - 3)(3x + 2) - (4x + 7)(x + 4)= (2x + 1)(5x - 1) - 33
Tìm x biết:
a) 4(18-5x) - 12(3x-7) = 15(2x-16) - 6(x+14)
b) 5(3x+5) - 4(2x-3) = 5x+3(2x+12)+1
c)2(5x-8) - 3(4x-5) = 4(3x-4) + 11
d) 5x-3 {4x-2 [4x-3(5x-2)]}=182
tìm x biết :
a) 2 . |5x-3| - 2x = 14
b) |3x-2| - x = 7
c) |4x+3| - x = 15
d) |3x-2| + 5x = 4x -10
e) |3x-2| + 5x = 4x-10
f) |2x-6| + 5x = 9
g) |5x-3| - x = 7
Tìm x biết:
a) 11/15 - (7/9 + x) × 3/8 = 61/90 + x/3
b) (4x + 1)(-2x + 1/3) = 0
c) 5x(2x - 1/2) + 2(2x - 1/2) = 0
: Tìm x, biết:
a) 3x( 4x- 1) - 2x(6x- 3 )=30 b) 2x(3-2x) + 2x(2x-1)=15
c) (5x-2)(4x-1) + (10x +3)(2x - 1)=1 d) (x+2) (x+2)- (x -3)(x+1) = 9
e) (4x+1)(6x-3) = 7 + (3x – 2)(8x + 9) g) (10x+2)(4x- 1)- (8x -3)(5x+2) =14
a, 2x( 3x + 1 ) + 3x ( 4 - 2x ) = 7
b, 4(18 - 5x ) - 12( 3x - 7 ) = 15(2x - 16 ) - 6(x + 14 )
c, ( 3x + 2 ) ( 2x + 9 ) - ( x + 2 ) ( 6x + 1 ) = ( x + 1 ) - ( x - 6 )
Tìm x
Tìm x biết
(2x-3)/(5x+6)=2/15
Tìm x, biết:
a. | 7 - x | - | 2x + 5 | < 2x - 3
b. | -5x + 3 | - | 2x - 3 | > x + 2
c. | 7x | + | -5x +9 | < 6
Tìm x, biết :
|5x - 4| = |x + 2|
|2x - 3| - |3x + 2| = 0
|5/4. x - 7/2| - | 5/8. x + 3/5| = 0
|7x + 1| - |5x + 6| = 0